Karakteristik Organoleptik Produk Krim dari Berbagai Formulasi Penambahan Konsentrasi Kolagen Kulit Ikan Nila - Junianto, Junianto; Pramesti, Adriana Putri (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Fish skin waste is one of the alternatives that can be used as raw materials for making collagen. Collagen has been widely used in the cosmetic industry. One of the cosmetics that utilizes collagen is cream. This study aims to determine the organoleptic characteristics of cream products from various formulations of added concentrations of fish skin collagen. This research was conducted experimentally consisting of two stages, namely cream making and organoleptic testing. The cream was made with four different treatments, namely the addition of tilapia skin collagen concentrations of 0%, 3%, 3.5%, and 4%. Organoleptic testing was analyzed statistically non-parametrically using the Friedman test and continued with a multiple comparison test. Based on the results of the study, namely the organoleptic characteristics of the selected cream products based on considerations of the preferred appearance of color, aroma and texture obtained from the treatment of adding a concentration of fish skin collagen of 3.5%. The level of preference for the appearance, color and texture of the cream obtained from the treatment of adding a concentration of fish skin collagen of 3.5% was not significantly different from the cream obtained from the treatment of adding a concentration of fish skin collagen of 4%. The level of preference for the aroma of the cream obtained from the treatment of adding a concentration of fish skin collagen of 3.5% was not significantly different from the cream obtained from the treatment of adding a concentration of fish skin collagen of 0%. The level of preference for the appearance, color and texture of the cream that was most preferred was obtained from the treatment of adding a concentration of fish skin collagen of 4% while the level of preference for the aroma that was most preferred was obtained from the treatment of adding a concentration of fish skin collagen of 0%. The results of this study are expected to be an innovation in the development of safe and halal cream products.